Sorption of fluorinated greenhouse gases in silica-supported fluorinated ionic liquids - Sosa, Julio E. (2022)
the contracts of Individual Call to Scientific Employment Stimulus 2020.00835.CEECIND (J.M.M.A.) / 2021.01432.CEECIND (A.B.P.), the Norma Transitória DL 57/2016. Publisher Copyright: © 2022 The Authors.